Development of the rope-climbing ergometer for physical training and testing - Arakawa, H.; Kumagawa, D.; Fujisaki, I.; Ozawa, Y.; Ishige, Y. (Sports Medicine International Open, 2017)
The purpose of this study was to develop and characterize a rope-climbing ergometer. A custom-made loading device that has an eddy current brake with an electrical current control circuit was developed to impose resistive load on the rope. A calibration test was first performed using a three-phase induction motor to associate the scale of the load-level setting (100 levels) with the resultant traction force. The calibration test yielded criteria values of loads (123 N at Level 0 and 1064 N at Level 100). The human test was carried out by 14 male subjects. The participants performed eight sets of 10-second maximal-effort exercises at different levels. Presumable trajectories of force, velocity, and power were obtained. The mean force increased by 161% (from 147.5 N at Level 0 to 383.7 N at Level 18), whereas the mean velocity decreased by 64.7% (from 1.87?m/s at Level 0 to 0.66?m/s at Level 18). The mean power reached its peak at Level 9 (320 W). The new rope ergometer for physical training and testing was successfully developed and characterized in this study. However, it remains to be seen whether its concurrent validity and reliability are qualifiable.